Neighbors again? Inter-Community Relations after Ethnic Violence - Čorkalo Biruški, Dinka; Ajduković, Dean; Weinstein, Harvey Stover, Eric; Đipa, Dino Biro, Mikloš (2004)
The study is based on a series of qualitative studies that were conducted in three war-torn communities – Vukovar, Mostar and Prijedor. First, we employed field studies in the cities of Vukovar and Mostar that began on September 2000 and lasted two years. Field data included analyses of perceptions of objective changes over time in the areas of reconstruction, economic growth, employment, schooling, health care, culture and sporting events, religion, media, civil society, safety, politics and everyday life. Second, in all three cities we conducted focus groups with representatives of war victims, NGOs, young people and entrepreneurs. The focus groups protocol addressed such issues as outcomes and consequences of the war, the role of the international community, the effects of war on physical and mental health, relations among ethnic groups before, during and after the war, problems of living in each city, war crimes, perceptions of the ICTY and reconciliation. Finally, we carried out key informant interviews in these cities to ascertain the opinions and attitudes of key community figures. Based on the principle of triangulation we were able to maximize the reliability and validity of our finding. The post-war period in the followed cities reflects uncertainty and an uneasy sense of transition. On the whole, we find that physical reconstruction has developed much faster than social renewal. Our data also suggest that social reconstruction must address at least four levels: individual, the level of community, the societal level and the state level in roder to build peaceful and stable communities.
Projekt MZOS
ENG